Effects of connection mode between carboxyl groups and main chains on polycarboxylate superplasticizer properties. Issue 6 (16th October 2012) - Lv, Shenghua; Ju, Haobo; Qiu, Chaochao; Ma, Yujuan; Zhou, Qingfang
Abstract Preparation and characterization of polycarboxylate superplasticizers of IPCs (copolymer of itaconic acid and allyl polyoxyethylene ether) and MPCs (copolymer of maleic anhydride and allyl polyoxyethylene ether) are shown. The difference between IPCs and MPCs is that half of the carboxyl groups of IPCs indirectly connect to the main chains through methylene. The effects of the carboxyl group‐main chain connection mode on the properties of IPCs and MPCs were investigated by assessing the paste fluidity and the pore diameters and compressive strength. The interaction between IPCs (MPCs) and cement were revealed by zeta‐potential and the adsorption amount. The results indicated that the indirect connection mode favorably improved paste fluidity, decreased pore diameters, and increased the compressive strength compared with the direct connection mode. This is likely because that when carboxyl groups are connected to the main chains indirectly, more moving space allows easier adsorption on cement particles. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013